التفريق القضائي بين الزوجين بسبب ضرب الزوجة في الولاية الفدرالية (برسكتون) كوالا لمبور : دراسة فقهية تطبيقية - Hanifah Binti Mazlan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research focuses on the issues of judicial divorce related to wife beating in the Federal Territory (Wilayah Persekutuan), based on statistics of cases registered in Kuala Lumpur Shariah Court. Furthermore, one of the main objectives of this study is to explain the concept and reality of wife-beating in light of Islamic family law of Wilayah Persekutuan, and it has also interpreted the concept of judicial divorce of spouse (husband and wife) related to wife-beating, and its entailing rulings according to Islamic Fiqh and Islamic Family Law of the Federal State (Persekutuan). In addition, this study aims to explore cases of wife-beating phenomenon that lead to judicial divorce based on the official statistics registered in the Shariah Court of Kuala Lumpur. The study also highlights suggestions made to prevent the unnecessary rise of divorce cases due to wife-beating. It is worth mentioning that inductive and analytical methods were used in this study. In conclusion on the finding show that wife-beating is due to numerous factors: financial problems, polygamy, bad morals among husbands, hot temper and madness of husbands. After discussing the cases of wife-beating, the study offers some recommendations that may contribute as solutions to the problem. Several suggestions are made to bring justice to victims of wife-beating.